2015
DOI: 10.1016/j.pocean.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Trends in anthropogenic CO2 in water masses of the Subtropical North Atlantic Ocean

Abstract: The variability in the storage of the oceanic anthropogenic CO 2 (C ant ) on decadal timescales is evaluated within the main water masses of the Subtropical North Atlantic along 24.5°N.Inorganic carbon measurements on five cruises of the A05 section are used to assess the changes in C ant between 1992 and 2011, using four methods (ΔC*, TrOCA, φC T 0 , TTD). We find good agreement between the C ant distribution and storage obtained using chlorofluorocarbons and CO 2 measurements in both the vertical and horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…The important difference in C ant between the two cruises within the AAIW stratum has also been recently noticed by Guallart et al (2015) along 24.5°N. In that study, the authors suggested that, regarding the C ant computation in the AAIW layer, it is important to consider that methods based on CO 2 measurements are particularly sensitive to changes in that water mass.…”
Section: Resultsmentioning
confidence: 65%
“…The important difference in C ant between the two cruises within the AAIW stratum has also been recently noticed by Guallart et al (2015) along 24.5°N. In that study, the authors suggested that, regarding the C ant computation in the AAIW layer, it is important to consider that methods based on CO 2 measurements are particularly sensitive to changes in that water mass.…”
Section: Resultsmentioning
confidence: 65%
“…During the 2011 cruise, under the umbrella of the Malaspina project (http://www.expedicionmalaspina.es), 167 full‐depth hydrographic stations were carried out, 13 of them in the Florida Straits [ Hernández‐Guerra et al ., ]. Bottle samples were collected to measure oxygen, nutrients, A T , and pH, and C T was calculated [ Guallart et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…[] and Guallart et al . [] defined their water masses in terms of isopycnal. Because of this, there is a small mismatch in the lower limit of the AAIW, located within the upper layer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations